Conducting composite films based on chitosan or sodium hyaluronate. Properties and cytocompatibility with human induced pluripotent stem cells - Jasenská, Daniela; Kašpárková, Věra; Radaszkiewicz, Katarzyna Anna; Capáková, Zdenka; Pacherník, Jiří; Trchová, Miroslava; Minařík, Antonín; Vajďák, Jan; Bárta, Tomáš; Stejskal, Jaroslav; Lehocký, Marián; Truong, Thanh Huong; et al. (Carbohydrate polymers, 2021)
Novel composite films combining biocompatible polysaccharides with conducting polyaniline (PANI) were prepared via the in-situ polymerization of aniline hydrochloride in the presence of sodium hyaluronate (SH) or chitosan (CH). The composite films possess very good cytocompatibility in terms of adhesion and proliferation of two lines of human induced pluripotent stem cells (hiPSC). Moreover, the cardiomyogenesis and even formation of beating clusters were successfully induced on the films. The proportion of formed cardiomyocytes demonstrated excellent properties of composites for tissue engineering of stimuli-responsive tissues. The testing also demonstrated antibacterial activity of the films against E. coli and PANI-SH was able to reduce bacterial growth from 2 × 105 to < 1 cfu cm-2. Physicochemical characterization revealed that the presence of polysaccharides did not notably influence conductivities of the composites being ∼1 and ∼2 S cm-1 for PANI-SH and PANI-CH respectively; however, in comparison with neat PANI, it modified their topography making the films smoother with mean surface roughness of 4 (PANI-SH) and 14 nm (PANI-CH). The combination of conductivity, antibacterial activity and mainly cytocompatibility with hiPSC opens wide application potential of these polysaccharide-based composites.
Keywords: Tissue Engineering; Nanocomposites; Conducting composites; Staphylococcus aureus; Chitosan; Humans; povrchové vlastnosti; tkáňové inženýrství; elektrická vodivost; Escherichia coli; Induced Pluripotent Stem Cells; Cell Adhesion; lidé; antibakteriální látky; proliferace buněk; polymerizace; Polymerization; buněčné linie; Biocompatible Materials; indukované pluripotentní kmenové buňky; Aniline Compounds; Anti-Bacterial Agents; Cell Line; Electric Conductivity; Cell Proliferation; kyselina hyaluronová; aniliny; Polyaniline; Human induced pluripotent stem cells; biokompatibilní materiály; buněčná adheze; Polysacharides; Hyaluronic Acid; chitosan; Surface Properties; nanokompozity